Globalization and Oral traditions - Athena Alchazidu (Obra Digital, 2020)
Indigenous orality represents an important part in the everyday life of the Ameriandian communities from the Ecuadorian Amazon region. It is important to see a symptom of serious threats in this phenomenon that can lead to the extinction of these indigenous languages. According to recent research, several languages spoken in the communities of Ecuador are considered to be in danger of extinction. Effective prevention can be promoted by academic projects focused on encouraging indigenous speakers of all generations to use the language regularly in ordinary situations. In this way, indigenous languages can become the language of instruction used in official educational institutions.